2022
DOI: 10.1371/journal.pone.0270893
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes after SARS-CoV-2 infection by trimester: A large, population-based cohort study

Abstract: Objectives Data regarding women infected with SARS-CoV-2 during early trimesters are scarce. We aimed to assess preterm birth (PTB) and small-for-gestational-age (SGA) rates in a large and unselected cohort by trimester at infection and overall. Design A retrospective cohort study including all women with a positive SARS-CoV-2 RT-PCR test during a non-ectopic singleton pregnancy between February 21st 2020 and July 2nd 2021 (N = 2753). Each infected woman was matched to a non-infected pregnant woman by age, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
2
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 31 publications
(43 reference statements)
6
26
2
4
Order By: Relevance
“…Recently, a large cohort study indicated that the SARS-CoV-2 infection during third trimester is significantly associated with preterm births as compared to matched non-infected controls. 100 First and second trimester infections did not cause any adverse pregnancy outcomes when compared to non-infected controls. This study emphasizes the importance of gestational age at SARS-CoV-2 infection in determining the outcome of the pregnancy.…”
Section: Preterm Births and Stillbirthsmentioning
confidence: 84%
“…Recently, a large cohort study indicated that the SARS-CoV-2 infection during third trimester is significantly associated with preterm births as compared to matched non-infected controls. 100 First and second trimester infections did not cause any adverse pregnancy outcomes when compared to non-infected controls. This study emphasizes the importance of gestational age at SARS-CoV-2 infection in determining the outcome of the pregnancy.…”
Section: Preterm Births and Stillbirthsmentioning
confidence: 84%
“… [7] , [10] , [11] , [12] , [13] , [14] , [16] , [18] , [19] , [30] , [31] , [33] , [36] , [38] , [53] Multiple studies report an increased risk of premature birth even after adjusting for common cofactors. [11] , [12] , [14] , [18] , [31] , [37] , [53] , [54] Preterm birth is also significantly more likely following COVID-19 in a high-risk pregnancy compared to an infection in a low-risk pregnancy. [28] In addition, several of these studies considered preterm birth in the context of infection severity with mixed reports on how COVID-19 severity impacted preterm birth risk.…”
Section: Maternal Sars-cov-2 Infection Impact On Maternal-fetal Outcomesmentioning
confidence: 99%
“…Babies born to people with COVID-19 during pregnancy weighed significantly less at delivery. [12] , [13] , [18] , [38] , [54] , [59] There were mixed reports about whether COVID-19 during pregnancy impacted the relative risk for SGA with one study reporting a 1.3 fold increase, [18] one study recording a 0.9 fold decrease, [59] and four noting no change ( Table 4 ). [12] , [13] , [30] , [54] Babies born to mothers with COVID-19 during pregnancy were also 1.2-2.4 fold more likely to be admitted to the NICU ( Table 4 ).…”
Section: Maternal Sars-cov-2 Infection Impact On Maternal-fetal Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…El riesgo de pequeño para edad gestacional fue comparable entre los grupos de estudio en todos los trimestres de la infección, y la pérdida del embarazo fue similar en ambos grupos. La infección por SARS-CoV-2 se asoció con un mayor riesgo de PPT solo entre las mujeres infectadas durante el último trimestre del embarazo, particularmente entre las mujeres sintomáticas (18) .…”
Section: Morbimortalidad Fetoneonatalunclassified